2022
DOI: 10.1515/cclm-2022-0105
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin in diabetes mellitus: a meta-analysis of diagnostic test accuracy

Abstract: Objectives Guidelines recommend the diagnosis of diabetes should be based on either plasma glucose or glycated hemoglobin (HbA1C) findings. However, lately studies have advocated glycated albumin (GA) as a useful alternative to HbA1c. We conducted a systematic review and meta-analysis to determine the overall diagnostic accuracy of GA for the diagnosis of diabetes. Content We searched for articles of GA diabetes diagnostic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As far as we know, this is the first study that evaluated the diagnostic accuracy of GA to detect diabetes in hospitalized individuals with COVID-19. However, our findings are supported by studies conducted in the general population that demonstrated very good GA performance for diabetes diagnosis [26][27][28][29][30]. In a systematic review and meta-analysis of diagnostic test accuracy, we showed that GA performed very well for diabetes diagnosis by oral glucose tolerance test with/without HbA1c in the non-hospitalized general population [26].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As far as we know, this is the first study that evaluated the diagnostic accuracy of GA to detect diabetes in hospitalized individuals with COVID-19. However, our findings are supported by studies conducted in the general population that demonstrated very good GA performance for diabetes diagnosis [26][27][28][29][30]. In a systematic review and meta-analysis of diagnostic test accuracy, we showed that GA performed very well for diabetes diagnosis by oral glucose tolerance test with/without HbA1c in the non-hospitalized general population [26].…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, all tests are equally appropriate to diagnose diabetes. In our study, the adequate cut-off to detect newly diagnosed diabetes was slightly higher than those reported in general population, where GA ranged between 15% to 18% to identify diabetes [26][27][28][29][30]. We did not explore time to admission from onset of COVID-19-related symptoms for this study.…”
Section: Plos Onementioning
confidence: 64%
See 1 more Smart Citation
“…Glycated hemoglobin reflects blood glucose control over the past three months. If a patient has high levels of glycated hemoglobin, it indicates poor blood glucose control, which in turn activates various pathways such as the polyol pathway, advanced glycation end products, and hexosamine pathway, further exacerbating endothelial cell damage in the lower limb blood vessels and worsening vascular injury [22,23]. Hyperlipidemia and atherosclerosis are local pathologic changes that occur after vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting early-stage glycation is vital for early monitoring and better intervention in aging-related deterioration [10] . Some well-known early-stage glycated markers, such as glycated hemoglobin and glycated albumin, have been utilized as indicators for blood glucose control monitoring, while early-stage glycated transferrin shows potential for monitoring blood glucose control and early diagnosis of diabetic nephropathy [ 15 , 20 , 21 ]. These findings underscore the importance of studying early-stage glycated proteins in biological processes.…”
Section: Introductionmentioning
confidence: 99%